The [un]knowing director: a critical examination of directing within the context of devising performance - Thulo, Kabi (School of Dance, 2022)
This thesis is a critical examination of directing within the context of devising performance practice. It emanates from my need to make sense of the particular ways in which I work as a theatre director who engages with devising performance coupled with an identified lack in the literature that speaks to directing and devising performance from a Southern African perspective. The notion of the [un]knowing director is posited as the central concept that is evidently plausible for the particular context of devising performance practice argued for in the thesis. The key argument expressed in this thesis is that [un]knowing is a way of knowing realised through intuition and collaboration as co-constitutive or symbiotic aspects applicable to the study's particular contexts of directing and devising performance practice. To be more specific, the study investigates how the [un]knowing director makes artistic discoveries and decisions/choices during the moment-to-moment unfolding of a devising process. The notion of the [un]knowing is conceptually explicated by drawing from Tim Ingold's ideas of wayfaring and wayfinding (2000 & 2011), Henri Bergson's (1907) philosophical conception of time understood as duration, and Leopold Senghor's Africanist philosophy that speaks of rhythmic attitude, reason-eye and reason embrace (Diagne, 2019). This thesis is located within the sphere of nonrepresentational theory and purports for knowledge, within the context of directing and devising performance, as an undertaking that is non-predetermined and emergent in character. In terms of its methodology, this study is generally located within the methodological terrain of qualitative research and specifically employs practice as research. Specifically, its methodology entailed a structured questionnaire responded to by seven Southern African devising performance directors. The questionnaire's general research aim was to identify the plausibility of the [un]knowing director concept based on other director's experiences of devising performance. Thereafter, three creative research projects in the form of devising performance processes, were undertaken. These projects served as related case studies constituting an investigative cycle. The research method of autoethnographical devising session note-taking and reflective accounts was used in generating the necessary data through the creative research projects. Essentially, this thesis concludes that the [un]knowing director knows through intuition and collaboration in ways that are particular to its critical examination of directing and devising performance. These two ways of knowing are complex in their nature and characterised by the elements of initiation, facilitation and decision making during the moment-to-moment unfolding of a devising session. Relatedly, this thesis refers to the [un]knowing director's momentary undertakings as the molecular, micro and macro levels of artistic activity. Ultimately, this thesis concludes that the [un]knowing director has a complex genealogy emanating from the Southern African oral performance tradition. Thus, the [un]knowing director's practice is story-like and significantly affected by time.